Twenty years of MALL project implementation: A meta-analysis of learning outcomes - Burston, Jack (My University, 2015)
Despite the hundreds of Mobile-Assisted Language Learning (MALL) publications over the past twenty years, statistically reliable measures of learning outcomes are few and far between. In part, this is due to the fact that well over half of all MALL-related studies report no objectively quantifiable learning outcomes, either because they did not involve MALL implementation projects, or if they did, learning gains were only based on subjective teacher assessments and/or student self-evaluations. Even more so, the paucity of statistically reliable learning outcome data stems from the short duration of projects and small numbers of students involved. Of the 291 distinct studies examined in this review only 35 meet minimal conditions of duration and sample size, i.e., ten experimental subjects over a period of at least a month. Sixteen of these suffer from serious design shortcomings, leaving only nineteen MALL studies that can reliably serve as a basis for determining the learning outcomes of mobile-based language applications. Of these studies, fifteen can be considered to report unequivocal positive results, with those focusing on reading, listening and speaking without exception evidencing a MALL application advantage. Four studies, all focusing on vocabulary, reported no significant differences.
Keywords: Grammar; Learning outcomes; Listening; MALL; Mobile-assisted learning; Reading; Speaking; Vocabulary acquisition; Writing